Improving the Labour Productivity through Applications of Work Study Principles: Enhancing Construction Industry Efficiency through Work Study Principles (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Civil is a basic branch of engineering and hence construction industry is one of the largest industry in economy. Because of its large presence, it contributes to the national economy and provides employment to the large no of people. Large amount of investment is made in the constructing ports, roads, urban infrastructural development, telecommunication sectors, power plants, and rural development etc. Various studies are performed by different researchers to improve the efficiency and effectiveness of construction process, implementation various techniques to reduce re-work and improve the productivity. Labour productivity is a very important factor in the construction industry that affects the overall quality of construction. Different labors have their own capacity of working and they show different level of productivity and affect the time and quality of the construction.Case studies and work measurement can improve the planning of human effectiveness. Using this study we can improve the efficiency and economy of the construction industry. Purpose of this work, focuses the benefits of time and method study employed in construction sectors. Method study and work measurement and work sampling has been used to measure the productivity of the various construction activities. It is expected that this concept will help to improve the further quality of the product and reduce risks.In essence, the focus is to apply method study and work measurement and statistical analysis to various construction activities to the observation data sets generated for different construction processes on site and determines their productivity processes and establish regression equation using statistical analysis.